Kaseba on Plane Shape Material to Improve Elementary School Students' Learning Outcomes - Ita Kurnia (JURNAL PENDIDIKAN DASAR NUSANTARA, 2026)
This study aims to measure the improvement in student learning outcomes after using the Kaseba (Polygonal Bag) learning media, determine the level of media effectiveness based on learning completeness, and determine the percentage of positive student responses in learning mathematics on plane geometry material. The study used a quasi-experimental method with a One Group Pretest–Posttest design involving 30 fourth-grade students from two elementary schools. The instruments used included a learning outcome test and a student response questionnaire. The results showed a significant increase in learning outcomes, indicated by an increase in the average score from 55.93 in the pretest to 91.43 in the posttest, with an N-Gain score of 0.81 which is included in the high category. Classical completeness reached 100%, so the Kaseba media was declared very effective for use in learning. In addition, the questionnaire results showed a student response of 90% with a very positive category, indicating that the Kaseba media is interesting, easy to use, and helps understand the concept of plane geometry concretely. Overall, this study concludes that Kaseba media is effective in improving learning outcomes, meeting classical completeness, and receiving positive appreciation from students, so it is worthy of being recommended as an alternative mathematics learning media in elementary schools.